Development and preliminary validation of four brief measures of L2 language-skill-specific anxiety. (August 2017) - Cheng, Yuh-show
Abstract: This paper reports a study on the development and validation of four brief measures of L2 language-skill-specific anxiety scales: L2 listening, speaking, reading, and writing anxiety scales. A total of 523 college students in Taiwan participated in the study. Lang's (1971) tripartite model of anxiety provided a theoretical basis for developing the four scales. An initial pool of items were developed based on a review of related literature and the results of a focus group interview. Less ideal items were removed based upon the results of a pilot test. In the formal study, exploratory factor analysis was conducted to select items for each anxiety scale, which was subsequently validated by confirmatory factor analysis and correlation analysis. The results provided evidence for the reliability, convergent validity, and discriminant validity of the scores of the four brief measures.